FACTORS RELATING TO NURSES' COMPLIANCE IN IMPLEMENTING THE SURGICAL SAFETY CHECKLIST : A SCOPING REVIEW - Ardhana, Putra; Haryanto (Nurse and Health: Jurnal Keperawatan, 2024)
Backround: One component of Safe procedure Saves Lives is a surgical safety checklist (SSC), which serves as a tool for the surgical team to utilize in the operating room to ensure that the procedure is both safe and of high quality, SSC compliance cannot be separated from the factors that influence it, therefore we need to know these factors to overcome SSC problems SSC compliance cannot be separated from the factors that influence it, therefore we need to know these factors to overcome SSC problems. This article aims to obtain a comprehensive picture of the factors related to nurse compliance in implementing the Surgical Safety Checklist. Design: This study uses the Arksey and O'Malley model to conduct the analysis. Data Source: The analyzed literature consisted of Scholar, Science Direct, and Pubmed from January 2016 to June 2023. Identification and selection of literature used Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) Moher 2009. Result: The results were 15 articles that were analyzed, consisting of 12 quantitative articles, two descriptive articles, and one literature review article. This article summarizes findings regarding compliance in implementing the Surgical Safety Checklist, including attitudes, perceptions, motivation, knowledge, time for operations, age, length of work, education, teamwork, and nurse compliance. Conclusion: There is a relationship between 10 factor include attitudes, perceptions, motivation, knowledge, time for operations, age, length of work, education, teamwork, and nurse compliance. in the implementation of SSC.